Addition of Garlic Solution (Allium sativum) and Isolate Pediococcus pentosacceus N6 Strain on Chemical Quality and Shelf Length of Goat Meat - Wiranda, Sulistio; Nurjama'yah Ketaren; Wahyudi Himawan Sutanto; Suhendra Pakpahan (Talenta Publisher, 2025)
Goat meat is one of the food ingredients of animal origin that is very beneficial for humans, because it is rich in protein, fat, vitamins and minerals. Preservation aims to protect goat meat from damage caused by various microbes such as bacteria, fungi, and so on. The use of chemical preservatives in food products is harmful to health. Therefore, research on natural preservatives that are safe for consumption by the public is needed. One natural ingredient that can be used is a garlic solution combined with Pediococcus pentosacceus strain N6. The experimental design for this study employs a Complete Randomized Design (CRD) with a 3x3 factorial pattern and three replications. As a result, there are a total of 27 experimental units. Factor I: Concentration of Garlic Solution + Pediococcus pentosacceus strain N6 P0: No Treatment, P1: Spraying using 30 ml of garlic solution + 10 ml of Pediococcus pentosacceus strain N6, P2: Spraying using 60 ml of garlic solution + 20 ml of Pediococcus pentosacceus strain N6. Factor 2: Storage time at room temperature (27°C), J1: 0 hours, J2: 24 hours, J3: 48 hours. Different doses and storage times resulted in the best meat quality in treatment P2 (60 ml garlic solution + 20 ml Pediococcus pentosacceus strain N6) with the highest average protein content of (21.88c ± 2.15) and the highest code in P2J1 (24.19g), the lowest fat content of (8.92 ± 1.59) with the lowest code in P2J3 (7.72), the lowest TPC value of (2.7 ± 1.39) with the lowest code in P2J1 (1.3), and the best color and aroma. In conclusion garlic solution combined with Pediococcus pentosacceus strain N6 could preserve goat meat